1963
DOI: 10.2466/pr0.1963.12.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Context Effects in Running Memory

Abstract: 7 groups of college-age Ss attempted to recall whether the next to last symbol was the “same” or “different” from the viewed symbol in a running series of 42 symbols. 6 of the groups also predicted the recall outcome on successive trials. Expectancy did not influence retention, but a negative recency effect sensitive to symbol runs resulted from predictions. Results from memory errors contradicted the concept of a fixed running recall-span. Evidence was found for (a) recall generalization to the symbol before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…Thus, the subjects retain only the most recent n items that are presented and continuously drop items from the maintenance/rehearsal set once the list length exceeds n. Similarly, the keeping-track task (Yntema & Mueser, 1960, 1962) presents a list of items, of unknown length and from n categories (the memory load), and subjects retain only the most recent exemplar of each category. Finally, the n-back task (Kirchner, 1958;Mackworth, 1959;Moore & Ross, 1963) presents a list of items in which the subject must continuously report whether each item matches the one that had appeared n items ago in the stream (n typically ranges from 1 to 4). In a two-back task, for example, subjects must continuously maintain the last 2 items in the list, updating this memory set with each new item and dropping out the least recent one.…”
Section: Wm Span Tasks Versus Other Wm Tasksmentioning
confidence: 99%
“…Thus, the subjects retain only the most recent n items that are presented and continuously drop items from the maintenance/rehearsal set once the list length exceeds n. Similarly, the keeping-track task (Yntema & Mueser, 1960, 1962) presents a list of items, of unknown length and from n categories (the memory load), and subjects retain only the most recent exemplar of each category. Finally, the n-back task (Kirchner, 1958;Mackworth, 1959;Moore & Ross, 1963) presents a list of items in which the subject must continuously report whether each item matches the one that had appeared n items ago in the stream (n typically ranges from 1 to 4). In a two-back task, for example, subjects must continuously maintain the last 2 items in the list, updating this memory set with each new item and dropping out the least recent one.…”
Section: Wm Span Tasks Versus Other Wm Tasksmentioning
confidence: 99%
“…n-back (Moore and Ross, 1963): a series of digits are presented; participants report the stimulus which was presented n-stimuli ago. To correctly perform this task participants must display the ability to hold information within the attentional system.…”
Section: Sustained Attentionmentioning
confidence: 99%
“…S was required to say whether each successively viewed symbol in a running, randomly ordered series was the "same" or "different" from the symbol seen a specified number of symbols back in the series, e.g., a 2-back match-back would require the next-the-last symbol. The present paper extends the work of an earlier study on "context effects in running memory" (Moore & ROSS, 1963) which first used this sunning matching memory ( R M M ) task. The previous srudy manipulated context by varying ( 1 ) the number of different symbols composing individual series of symbols and ( 2 ) the different symbol combinations occurring within a symbol series.…”
Section: Serial Order Asmentioning
confidence: 92%
“…The previous study (Moore & Ross, 1963) showed that serial order produces several systematic memory errors. The more comprehensive aim of the present study is to show that serial order is a anique source of error in running memory.…”
Section: Serial Order Asmentioning
confidence: 98%